Examining Factors Affecting Intention to Play Video Games: Study of the Indonesian Game Industry - Zulfaikar Fachreza; Widi Senalasari; Lina Setiawati; Fatya Alty Amalia (Politeknik Negeri Bandung, 2022)
Video games become one of the entertainment media that grabs peoples’ interest along with the development of technology. It forms in several platforms, such as personal computers, consoles, and mobile. As one of the potential target markets for games, Indonesia is still struggling to compete with foreign games to dominate the local market. This study aims to determine the factors influencing the intention to play video games. This research is also intended to help the local developers in developing their games. This research employs the Uses and Gratification Theory and Technology Acceptance Model, supported by Factors in Game. This study uses a quantitative approach involving 311 respondents by distributing online questionnaires to foreign and local gamers who play online and offline games. The results show that escape, challenges, perceived ease of use, and perceived usefulness indirectly influence the intention to play through perceived enjoyment. Meanwhile, trust in game developers has a direct influence on the intention to play.